Determinantes e consequentes da rotatividade dos servidores técnico-administrativos no campus IV da UFPB - Araújo, Walter Junior Leitão de (2024)
This study aimed to investigate the determinants and consequences of internal turnover among technical-administrative staff at Campus IV of the Federal University of Paraíba (UFPB).Located on the northern coast of Paraíba, Campus IV has an insufficient team and a high turnover rate among its administrative technicians. To address this issue, specific objectives were established, including identifying the factors influencing the decision of administrative technicians to transfer to other UFPB centers, evaluating the impacts of turnover on campus management from the perspective of managers, and proposing management actions and strategies to mitigate these effects. Based on a literature review, a theoretical framework was structured, containing studies on the determinants of turnover in public and private organizations. The research began with a documentary analysis, collecting data on the evolution of the staff from 2015 to 2022 and information on removal notices up to 2024, which directly impact turnover at the center. From the organizational factors identified in the theoretical framework, interview scripts were developed for administrative technical staff and managers of Campus IV to explore their experiences and perceptions regarding psychological factors and the organizational environment. Using a qualitative approach, the research involved semi-structured interviews and documentary analysis to investigate turnover. Data analysis identified recurring patterns and themes, which were contrasted with the theoretical references. The inclusion of narrative analysis valued the participants' experiences and provided valuable insights for human resource management, allowing a comprehensive understanding of the phenomenon and proposing actions and strategies to mitigate its negative effects. The results reveal that high turnover affects commitment and trust among staff, recommending flexible schedules, remote work, and the restructuring of rewarded positions. Improvements in management policies and internal communication are also suggested to increase staff satisfaction and stability. It is expected that this research will provide valuable information to the university, enabling improvements in working conditions and a reduction in turnover, demonstrating its academic relevance and social impact, while offering practical guidelines as a generated product, relevant to more effective human resource management at Campus IV of UFPB.